Supported catalyst and method for preparing allyl alcohol block polyether by using same
By using a silica gel-laden zinc-nickel catalyst and a strong base catalyst, the problems of high cost and complex processes in the preparation of allyl alcohol block polyether are solved, and products with high double bond retention and low allyl content are achieved, which simplifies the process and Improved product quality.
Patent Information
- Application Number
- CN202411343491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The prior art has high cost, complex processes and metal ion residue problems in the preparation process of allyl alcohol block polyethers, which affect catalytic activity and product quality.
A supported catalyst, including silica gel, is prepared by heating calcination, and epoxidation reaction is carried out in combination with a strong alkali catalyst to prepare allyl alcohol block polyethers with high double bond retention and low allyl content.
The process flow is simplified, costs are reduced, product quality is improved, and the selectivity of zinc-nickel catalysts reduces epoxy isomerization and retains high double bond content.
Smart Images

Figure BDA0005060343940000051 
Figure BDA0005060343940000052 
Figure BDA0005060343940000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyether preparation, and particularly relates to a supported catalyst and a method for preparing allyl alcohol block polyether by using the supported catalyst. Background Art
[0002] Allyl alcohol block polyoxyethylene polyoxypropylene ether is mainly used for silicone oil graft modification. Allyl alcohol polyether and hydrogen-containing silicone oil are synthesized into polyether-modified polysiloxane under the action of catalyst. The siloxane main chain in polyether-modified polysiloxane acts as a hydrophobic group, giving the product excellent stability, anti-aging, electrical insulation, softness and other properties, while the hydrophilic polyether segment gives the product good surface activity.
[0003] At present, there are many studies on allyl alcohol block polyethers. For example, patent CN1974630A discloses a method for preparing a medium-high molecular weight allyl alcohol polyether unit alcohol, which uses a monofunctional allyl polyether unit alcohol containing double bonds with a molecular weight of 300-1000 as an initiator and double metal cyanide (DMC) as a catalyst to synthesize allyl alcohol polyethers with a molecular weight of 2000-5000 at a temperature of 100-160° C. The advantage of this method is that it can synthesize high molecular weight polyethers, but the disadvantage is that the synthesized polyethers affect the catalytic activity of chloroplatinic acid when reacting with hydrogen-containing silicone oil due to residual metal ions, making the catalytic activity of chloroplatinic acid inactivated, and the amount of catalyst needs to be increased. In addition, when the synthesized polyether-modified silicone oil is used as a foaming agent for polyurethane soft foam foaming, the foam opening is uneven, which affects the product quality.
[0004] Patent CN117326919A provides a method for preparing ultra-low molecular weight capped polyethers suitable for textile auxiliaries. It includes the following steps: reacting allyl alcohol with alkylene oxide under the action of sodium hydride catalyst to obtain a basic polyether; reacting the basic polyether with an alkylating capping agent under the action of an alkaline catalyst to obtain a crude product of allyl alcohol alkyl capped polyether polyol; and washing the crude product of allyl alcohol alkyl capped polyether polyol with water, neutralizing it with acid, adsorbing it, drying it, filtering it, and refining it. This preparation method can produce ultra-low molecular weight capped polyethers with high yield. Polyether, metal ions are easily removed during the preparation process, and the metal ions in the obtained product The content is low. However, the process The operation is complicated and tedious, and still requires post-processing, and the process cost is high. Therefore, finding a preparation method of allyl alcohol block polyether with high double bond retention rate, high product quality and simple process route has become the focus of current research. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a supported catalyst and a method for preparing an allyl alcohol block polyether using the supported catalyst. The supported catalyst provided by the present invention can prepare high-quality allyl alcohol block polyether with high double bond retention rate and low allyl content; and the use of the supported catalyst in preparing the allyl alcohol block polyether can simplify the process and reduce the cost.
[0006] The invention provides a supported catalyst.
[0007] Specifically, a supported catalyst includes silica gel and zinc and nickel supported on the silica gel; the mass ratio of the zinc to the nickel is (2-8): (2-8).
[0008] Preferably, the mass ratio of the zinc to the nickel is 2:(2-8).
[0009] Preferably, the mass of the silica gel is 20%-100% of the total mass of the zinc and the nickel; further preferably, the mass of the silica gel is 20%-80% of the total mass of the zinc and the nickel; more preferably, the mass of the silica gel is 20%-50% of the total mass of the zinc and the nickel.
[0010] The invention also provides a method for preparing the supported catalyst.
[0011] Specifically, the method for preparing the supported catalyst comprises the following steps:
[0012] The silica gel is mixed with zinc and nickel, and calcined at elevated temperature to obtain a supported catalyst.
[0013] Preferably, the temperature-raising calcination process is to heat the temperature to 450-650°C at a heating rate of 1-4°C / min, and then keep it warm for 8-18 hours; further preferably, the temperature-raising calcination process is to heat the temperature to 500-650°C at a heating rate of 2-4°C / min, and then keep it warm for 10-15 hours; more preferably, the temperature-raising calcination process is to heat the temperature to 550-650°C at a heating rate of 2.5-3.5°C / min, and then keep it warm for 10-12 hours.
[0014] Preferably, the silica gel is pre-treated before being mixed with the zinc and the nickel. The pre-treatment process is: grinding the silica gel, sieving, and then drying for standby use. The sieving process uses a filter screen with a pore size of 1mm-2mm.
[0015] Preferably, the drying process is carried out in an oven at 80-100° C. for 4-6 hours.
[0016] The invention also provides a method for preparing the allyl alcohol block polyether.
[0017] Specifically, a method for preparing an allyl alcohol block polyether comprises the following steps:
[0018] Allyl alcohol is used as a raw material, and an addition reaction is carried out with ethylene oxide under the action of a strong base catalyst to obtain an allyl alcohol polyoxyethylene ether intermediate; then, under the action of the above-mentioned supported catalyst, a secondary addition reaction is carried out with propylene oxide to obtain an allyl alcohol block polyether (allyl alcohol block polyoxyethylene polyoxypropylene ether).
[0019] Preferably, the molar ratio of the allyl alcohol to the ethylene oxide is 1:(2-50).
[0020] Preferably, the temperature of the primary addition reaction is 100°C-105°C, the time of the primary addition reaction is 2-5h, and the reaction is carried out until the pressure substantially does not change (the judgment standard is that the pressure decrease is not greater than 0.02Mpa in 10 minutes).
[0021] Preferably, the strong base catalyst is a mixture of one or more of KOH, NaOH, KOCH3, and NaOCH3.
[0022] Preferably, the mass of the strong base catalyst is 1‰-3‰ of the mass of the allyl alcohol polyoxyethylene ether intermediate.
[0023] Preferably, the mass of the supported catalyst is 0.3‰-6‰ of the mass of the allyl alcohol block polyether. Further preferably, the mass of the supported catalyst is 0.5‰-5‰ of the mass of the allyl alcohol block polyether; more preferably, the mass of the supported catalyst is 1.0‰-2.5‰ of the mass of the allyl alcohol block polyether.
[0024] Preferably, the molar ratio of the allyl alcohol to the propylene oxide is 1:(2-50).
[0025] Preferably, the temperature of the secondary addition reaction is 100°C-105°C.
[0026] More specifically, a method for preparing an allyl alcohol block polyether comprises the following steps:
[0027] Put allyl alcohol and a strong base catalyst into a reaction kettle, replace the N2 in the kettle, heat it to 100°C-105°C, slowly drop ethylene oxide into the kettle, wait until the drop of ethylene oxide is complete, and ripen the reaction at a temperature of 100°C-105°C for 2-5 hours until the pressure basically does not change (the judgment standard is that the pressure decrease is not more than 0.02Mpa in 10min), cool it down and degas, and obtain an allyl alcohol polyoxyethylene ether intermediate;
[0028] The allyl alcohol polyoxyethylene ether intermediate and the supported catalyst are put into a reaction kettle, and the N2 in the kettle is replaced; after dehydration for 1 hour under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, the temperature is lowered, and propylene oxide is slowly added to the kettle. After the epoxy addition is completed, the reaction is aged at a temperature of 100°C-105°C for 2-5 hours until the pressure basically does not change (the judgment standard is that the pressure decrease is not more than 0.02Mpa in 10min), and after cooling and degassing, allyl alcohol block polyoxyethylene polyoxypropylene ether (allyl alcohol block polyether) is obtained.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention provides a supported catalyst, including silica gel and zinc and nickel supported on the silica gel. Zinc and nickel can be firmly combined with silica gel without the risk of peeling. The catalyst not only combines the excellent thermal stability of zinc and the strong corrosion resistance and chemical stability of nickel; the supported carrier is loose and porous, has a large specific surface area, and has an adjustable pore size. During the reaction, the epoxide and the reaction substrate can have more contact area, thereby accelerating the reaction process. At the same time, the zinc ion shows strong selectivity during the reaction, and the ring-opening reaction of epoxy occurs alone, thereby greatly reducing the occurrence of epoxy isomerization. Therefore, the propylene content will be extremely low. And by controlling the ratio of zinc and nickel, the catalyst can well protect the double bond from breaking during the reaction process and participate in the reaction, so that the synthesized allyl alcohol block polyoxyethylene polyoxypropylene ether has a higher double bond retention rate and excellent product quality.
[0031] (2) The supported catalyst provided by the present invention can prepare high-quality allyl alcohol block polyether with high double bond retention rate and low allyl content; and it has low cost, simple preparation method, strong stability, and is easy to recycle and use the catalyst.
[0032] (3) The preparation method of the allyl alcohol block polyether provided by the present invention has a simple process, does not require complicated post-treatment, and has low process cost. DETAILED DESCRIPTION
[0033] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0034] Unless otherwise specified, the raw materials, reagents or devices used in the following examples and comparative examples can be obtained from conventional commercial sources or by existing known methods.
[0035] 1. In the following examples and comparative examples, the calculation formula for the double bond retention rate is as follows, in percentage (%):
[0036]
[0037] Where:
[0038] IV1——actual iodine value, measured in accordance with the provisions of GB / T13892-2020;
[0039] IV2——theoretical iodine value, obtained by formula (2).
[0040] Theoretical iodine value:
[0041]
[0042] Where:
[0043] 100——conversion factor;
[0044] 254 – the molar mass of iodine in grams per mole (g / mol);
[0045] 56110 - conversion factor, in terms of potassium hydroxide (KOH), milligrams of potassium hydroxide per mole (mg / mol);
[0046] OHV——Hydroxy value of the sample, measured by GB / T12008.3-2009.
[0047] 2. The method for determining the propylene content is as follows:
[0048] 2.1 Preprocessing
[0049] Weigh 5-7g of sample, add 50ml of methanol to the two conical flasks containing the sample and the blank conical flask respectively, stir well to completely dissolve the sample, use a pipette to accurately measure 20ml of the solution into each conical flask, and shake well.
[0050] 2.2 Titration
[0051] Rapidly titrate the sample with 0.1 mol / L sodium thiosulfate standard solution. At the beginning of the titration, keep dripping the sodium thiosulfate standard solution in a linear shape. When the color turns light yellow, start adding the sodium thiosulfate standard solution dropwise. When the yellow color no longer appears within 15 seconds, it is the end point of the reaction. Record the volume of the sodium thiosulfate standard solution.
[0052] 2.3 Result calculation
[0053] W = (Vo-V1) × C × 4.1 ÷ 2m;
[0054] W---the value of the propylene content, in percentage (%);
[0055] V0---the volume of blank consumed sodium thiosulfate standard solution, in milliliters (mL);
[0056] V1---The volume of sodium thiosulfate standard solution consumed by the sample, in milliliters (mL);
[0057] C---the concentration of sodium thiosulfate standard solution, in moles per liter (mol / L);
[0058] m---sample weight, in grams (g).
[0059] Example 1
[0060] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0061] The preparation method of the supported catalyst is as follows:
[0062] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the temperature was calcined and kept warm for 12 hours, and the zinc-nickel supported silica gel catalyst was successfully prepared.
[0063] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0064] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor. After replacing the N2 in the reactor 3 times, the temperature was raised and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0065] Take 427.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 0.8g of the supported catalyst prepared in Example 1 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1173.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.6%, and the propylene content is 0.018%.
[0066] Example 2
[0067] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0068] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 50:50, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0069] The preparation method of the supported catalyst is as follows:
[0070] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 50:50), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0071] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0072] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0073] Take 320.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 0.8g of the supported catalyst prepared in Example 2 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1280.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.3%, and the propylene content is 0.023%.
[0074] Example 3
[0075] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0076] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 80:20, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0077] The preparation method of the supported catalyst is as follows:
[0078] After the silica gel particles were fully ground, large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 80:20), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0079] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0080] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0081] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 0.8g of the supported catalyst prepared in Example 3 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 96.4%, and the propylene content is 0.047%.
[0082] Example 4
[0083] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0084] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0085] The preparation method of the supported catalyst is as follows:
[0086] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0087] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0088] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0089] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 0.8g of the supported catalyst prepared in Example 4 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 96.8%, and the propylene content is 0.027%.
[0090] Example 5
[0091] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0092] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0093] The preparation method of the supported catalyst is as follows:
[0094] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0095] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0096] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0097] Take 320.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Example 5 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1280.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 98.2%, and the propylene content is 0.014%.
[0098] Example 6
[0099] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0100] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 50:50, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0101] The preparation method of the supported catalyst is as follows:
[0102] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 50:50), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0103] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0104] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0105] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Example 6 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 96.7%, and the propylene content is 0.030%.
[0106] Example 7
[0107] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0108] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 80:20, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0109] The preparation method of the supported catalyst is as follows:
[0110] After the silica gel particles were fully ground, large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 80:20), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0111] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0112] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0113] Take 427.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Example 7 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1173.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.4%, and the propylene content is 0.025%.
[0114] Example 8
[0115] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0116] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0117] The preparation method of the supported catalyst is as follows:
[0118] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0119] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0120] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0121] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Example 8 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.6%, and the propylene content is 0.015%.
[0122] Example 9
[0123] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0124] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0125] The preparation method of the supported catalyst is as follows:
[0126] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0127] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0128] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0129] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 8.0g of the supported catalyst prepared in Example 9 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.1%, and the propylene content is 0.028%.
[0130] Example 10
[0131] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0132] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 50:50, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0133] The preparation method of the supported catalyst is as follows:
[0134] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 50:50), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0135] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0136] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0137] Take 427.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 8.0g of the supported catalyst prepared in Example 10 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1173.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.5%, and the propylene content is 0.013%.
[0138] Embodiment 11
[0139] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0140] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 80:20, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0141] The preparation method of the supported catalyst is as follows:
[0142] After the silica gel particles were fully ground, large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 80:20), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0143] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0144] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0145] Take 320.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 8.0g of the supported catalyst prepared in Example 11 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1280.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.2%, and the propylene content is 0.021%.
[0146] Example 12
[0147] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0148] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 20:80, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0149] The preparation method of the supported catalyst is as follows:
[0150] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 20:80), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0151] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0152] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0153] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 8.0g of the supported catalyst prepared in Example 12 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115°C-120°C, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100°C-105°C for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The measured double bond retention rate is 97.4%, and the propylene content is 0.020%.
[0154] Table 1 Allyl alcohol block polyether indexes
[0155]
[0156] From the data analysis in the table, it can be seen that when the catalyst content is 2%, the double bond retention rate is higher than that of catalysts with other contents, and the propylene content is also lower. As the molecular weight increases, the corresponding double bond retention rate begins to decrease. At the same time, through the comparative analysis of the metal content in the supported catalyst, it can be seen that when the zinc and nickel content is 2:8, the product index is the best and the application performance is the most excellent.
[0157] Comparative Example 1
[0158] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0159] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0160] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of KOH catalyst and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115℃-120℃, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100℃-105℃ for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The double bond retention rate and the propylene content were measured to be 80.2% and 0.30%.
[0161] Comparative Example 2
[0162] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0163] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0164] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and put it into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115℃-120℃, cool to 80℃, add 3.2g of DMC catalyst to the reactor and replace the N2 in the reactor 3 times, heat up, slowly drop 1344.0g of propylene oxide into the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100℃-105℃ for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The double bond retention rate and propylene content of the measured indicators are 92.0% and 0.10%.
[0165] Comparative Example 3
[0166] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0167] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 5:95, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0168] The preparation method of the supported catalyst is as follows:
[0169] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 05:95), and programmed temperature was calcined. After the temperature was raised to 600°C at a rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0170] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0171] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0172] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Comparative Example 3 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115℃-120℃, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100℃-105℃ for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The double bond retention rate and the propylene content were measured to be 94.3% and 0.030%.
[0173] Comparative Example 4
[0174] A supported catalyst comprising silica gel and zinc and nickel supported on the silica gel;
[0175] A supported catalyst comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of zinc to nickel is 95:5, and the total mass of zinc and nickel is 3 times the mass of the silica gel.
[0176] The preparation method of the supported catalyst is as follows:
[0177] After the silica gel particles were fully ground, the large particles were filtered with a filter screen with a pore size of 1 mm, and then dried in an oven at 100°C for 4 hours. Then 1g of the dried silica gel particles was mixed evenly with 3g of a zinc-nickel metal mixture (the mass ratio of zinc to nickel was 95:05), and programmed temperature was calcined. After the temperature was programmed to 600°C at a heating rate of 30°C / 10min, the zinc-nickel supported silica gel catalyst was successfully obtained after calcination and heat preservation for 12 hours.
[0178] A method for preparing an allyl alcohol block polyether comprises the following steps:
[0179] 116.0g of allyl alcohol and 1.6g of catalyst KOH were put into a 2.5L reactor, the N2 in the reactor was replaced 3 times, the temperature was raised, and 1484.0g of ethylene oxide was slowly added to the reactor. After the addition of ethylene oxide was completed, the reaction was aged at 100°C-105°C for 3 hours until the pressure basically stopped changing. After cooling and degassing, the allyl alcohol polyoxyethylene ether intermediate was successfully obtained.
[0180] Take 256.0g of the above-mentioned allyl alcohol polyoxyethylene ether and 3.2g of the supported catalyst prepared in Comparative Example 4 and put them into a 2.5L reactor, replace the N2 in the reactor 3 times, dehydrate for 40min under a vacuum degree of ≥0.097MPa and an environment of 115℃-120℃, cool down, slowly add 1344.0g of propylene oxide to the reactor, wait until the epoxy addition is completed, and ripen and react at a temperature of 100℃-105℃ for 3 hours until the pressure basically does not change, cool down and degas, and successfully obtain the finished product of allyl alcohol block polyoxyethylene polyoxypropylene ether. The double bond retention rate and the propylene content were measured to be 93.1% and 0.033%.
[0181] Table 2 Comparative Example Allyl Alcohol Block Polyether Index
[0182]
[0183] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A supported catalyst, characterized in that The invention comprises silica gel and zinc and nickel supported on the silica gel; the mass ratio of the zinc to the nickel is (2-8): (2-8).
2. The supported catalyst according to claim 1, characterized in that The mass ratio of the zinc to the nickel is 2:(2-8).
3. The supported catalyst according to claim 1 or 2, characterized in that The mass of the silica gel is 20%-100% of the total mass of the zinc and the nickel; preferably, the mass of the silica gel is 20%-80% of the total mass of the zinc and the nickel.
4. The method for preparing a supported catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: The silica gel is mixed with zinc and nickel, and calcined at elevated temperature to obtain a supported catalyst.
5. The preparation method according to claim 4, characterized in that: The process of temperature-raising calcination is to raise the temperature to 450-650°C at a heating rate of 1-4°C / min and then keep the temperature for 8-18h; preferably, the process of temperature-raising calcination is to raise the temperature to 500-650°C at a heating rate of 2-4°C / min and then keep the temperature for 10-15h.
6. A method for preparing an allyl alcohol block polyether, characterized in that: The following steps are involved: Allyl alcohol is used as a raw material, and an addition reaction is carried out with ethylene oxide under the action of a strong base catalyst to obtain an allyl alcohol polyoxyethylene ether intermediate; Then, under the action of the supported catalyst described in any one of claims 1 to 3, a secondary addition reaction is carried out with propylene oxide to obtain the allyl alcohol block polyether.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the allyl alcohol to the ethylene oxide is 1:(2-50).
8. The preparation method according to claim 6, characterized in that: The mass of the strong base catalyst is 1‰-3‰ of the mass of the allyl alcohol polyoxyethylene ether intermediate.
9. The preparation method according to claim 6, characterized in that: The mass of the supported catalyst is 0.3‰-6‰ of the mass of the allyl alcohol block polyether.
10. The preparation method according to claim 6, characterized in that: The molar ratio of the allyl alcohol to the propylene oxide is 1:(2-50).
Citation Information
Patent Citations
Preparation method of ultra-low molecular weight terminated polyether suitable for textile auxiliary agent
CN117326919A
Prepn process of high and medium molecular weigh polyether allyl monoalcohol
CN1974630A
Supported paint U-Ni-A catalyst and preparation process thereof
CN103272605A
Production of higher alpha-branched fatty acid
JP1994122649A
